Characterization of New Natural Cellulosic Fiber from Coconut Tree Primary Flower Leaf Stalk Fiber (CPFLSF). Issue 11 (2nd November 2021) - Thirumurugan, Rama; Jayaraj, M.; Shanmugam, D.; Ramkumar, T.
ABSTRACT: The properties of the chemical, physical, mechanical, thermal(TG & DSC), microscopic analysis(SEM), x-ray diffraction(XRD), Fourier-transform infrared spectroscopy(FTIR) of raw and alkali treated coconut tree primary flower leaf stalk fiber (CPFLSF) are reported for the first time in this work. Different percentages of NaOH such as 2%, 4%, and 6% are used to treat the extracted fibers to explore the influence of alkali treatment over the properties of the fibers. FTIR analysis reveals that the cellulose and wax content was found to reduce while increasing the NaOH concentration. The tensile test results showed that CPFLSF treated with 6% NaOH exhibited better tensile properties in the range of 2008–2653 MPa. The XRD for the CPFLSF treated with 6% NaOH showed the crystallinity index of 40.12% crystallinity size of 27.25 nm. Thermogravimetric analysis reveals that CPFLSF-6% is thermally stable up to 250°C.Scanning electron microscopy analysis revealed the presence of impurities over the surface of the raw fiber and found that these impurities are minimized when CPFLSF is treated with high concentration of NaOH, which leads to the enhancement of properties. The work provides a way to manufacturing a polymer matrix composite for light load automotive application.